Design Project-Based Learning Multimedia for Vocational Education Students - Henry Iskandar; Dwiki Muda Yulanto; Indra Koto; Marlan Marlan (Universitas Sultan Ageng Tirtayasa, 2022)
This study aims to change activities in the technical implementation of project-based learning in vocational education. Real-life learning activities packaged in project-based learning multimedia are believed to be able to foster student creativity. The technique of preparing learning multimedia is designed using the Instructional Successive Approximation Model (SAM I) because it is more flexible. Data collection techniques were obtained from a survey of multimedia learning needs analysis in pneumatic, hydraulic engineering (N=10), and cooling systems (N=10). The learning multimedia design was evaluated through content validity tests by experts totaling (N=4). The needs analysis results showed that most students did not use multimedia, and they used several methods to develop creativity into products, so multimedia was needed. The results of another study through the content validity test obtained learning multimedia evaluation data with an average score of the quality of learning design and quality of learning multimedia engineering (0.84) that met the